2020
DOI: 10.1001/jamadermatol.2020.1157
|View full text |Cite
|
Sign up to set email alerts
|

Calcinosis Cutis in the Setting of Chronic Skin Graft-Versus-Host Disease

Abstract: cluded. One patient who did not adhere to topical corticosteroid therapy and 3 patients with less than 5 years of follow-up (or loss to follow-up) were excluded. In the remaining 11 patients, mean age at diagnosis of primary lesion was 62.9 years (range, 26-88 years). Initial management of vSCC or dVIN included surgical excision alone in 4 patients, surgical excision with node biopsy in 2 patients, surgical excision with node dissection in 4 patients, and surgical excision with adjuvant laser therapy in 1 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A total of 410 articles were retrieved from the search. Additionally, ten more studies were added after the manual screening of the reference sections [ 10 , 17 25 ]. Eight articles were excluded at the eligibility stage due to reporting patients described in other included studies [ 20 , 26 , 27 ] or insufficient data [ 24 , 25 , 28 – 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 410 articles were retrieved from the search. Additionally, ten more studies were added after the manual screening of the reference sections [ 10 , 17 25 ]. Eight articles were excluded at the eligibility stage due to reporting patients described in other included studies [ 20 , 26 , 27 ] or insufficient data [ 24 , 25 , 28 – 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ten more studies were added after the manual screening of the reference sections [10,[17][18][19][20][21][22][23][24][25]. Eight articles were excluded at the eligibility stage due to reporting patients described in other included studies [20,26,27] or insufficient data [24,25,[28][29][30]. In the selection process, 40 records met the eligibility criteria and were included in this systematic review (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…33,34 Lastly, Saardi et al recently reported GVHD-associated calcinosis cutis development in seven post-HSCT patients, and calcinosis cutis has been most commonly associated with systemic sclerosis, a condition that shares many phenotypic features with skin GVHD. 35 Further work will be needed to clarify if elevated AT1R-AA levels contribute to this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…While no large-scale retrospective study has identified a clear association between ANA and CC, numerous case reports and series have found a potential link. A case series of patients with chronic graft-versus-host disease found that four out of five patients with CC had elevated ANA titers [81]. Diffuse CC has been described in patients with Sjogren's syndrome and SLE with positive ANA [82,83].…”
Section: Other Autoimmune Diseasesmentioning
confidence: 99%